The evolution of intelligent systems how molecules became minds - Richardson, Ken (Palgrave MacMillan, 2010)
How did we get from unconscious material forces to the dazzling intricacy of the human mind? Standard evolutionary theory has not provided us with a continuous picture of that long emergence. In consequence, psychological theories remain highly fragmented, without deeper roots or foundations, while the general public either remain confused, or invoke miracles or the hand of an intelligent designer. This book provides new concepts from dynamic systems theory, and the new evolutionary synthesis, to present a comprehensive overview of the evolution of cognition. It combines ideas about complexity and environmental structure to highlight the emergence of intelligent systems very early in evolution. Intelligent systems came to dominate evolution through increasing complexity, including cell signalling, epigenetics, developmental systems, behaviour, brain and cognitive systems, to culminate in the human cognitive and other mental systems. This volume has fundamental implications for psychological theory and our understanding of humanity